The Effect of Polydeoxyribonucleotide on Chronic Non-healing Wound of an Amputee: A Case Report - Shin, Junho (Ann Rehabil Med, 2018)
Polydeoxyribonucleotide (PDRN) is safe and effective in wound healing, cellular growth, synthesis of extracellular matrix protein, and inflammation reduction via activation of adenosine A2 receptors. We report a 28-year-old male patient treated with PDRN injections for chronic non-healing wound refractory to negative pressure wound therapy, skin graft, or growth factors. Three injections of PDRN were administered at the wound site into the anterior and medial sides of the left stump on the 1st, 4th, and 9th days of hospitalization. The PDRN ameliorated wound healing by enhancing cell growth, tissue repair, and angiogenesis. PDRN application represents a potential treatment for non-healing wounds obviating the need for additional therapies, and hospitalization, as well as improve patient’s activities of daily living.